Strange phonetic terms of the ancients (Journal of Imam Al-Kadhim College, 2023)
This research is concerned with studying the strange phonemic term of the ancients. As the ancient linguists put terms for all phonetic adjectives, exits, etc. Some of these terms were widely used after them, and some of them were rare or extinct in idiomatic use. This last we collected  Under the name of (strange phonetic terms), the field of our research was (the books of ancient linguists and intonation) and what was mentioned in them of these strange terms. In this research, we studied (thirty-six) strange terms. We  arranged them alphabetically and defined them in language and idiomatically. We presented the research with an introduction in which we summarized what we have done in this research, and a conclusion in which we summarized all our findings and recommendations.
Keywords: Keywords : jihad, violence, anthropology, Quranic vision